SEBUAH KAJIAN MORFOLOGI GENERATIF DALAM â€œSATUA BALI TALES FROM BALIâ€ - I Gusti Ayu Agung Dian Susanthi (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2017)
[Title: A Generative Morphology Study in â€˜Satua Bali Tales from Bali'] The diversity and uniqueness of language in the world is an interesting linguistic phenomenon to be studied. Word formation is one of interesting research object, because every language of course has diversity in word formation which is called as morphology process. The theory used in this paper is a theory that is written by experts in the field of morphology. The theory used is the theory of morphology, namely: the theory of generative morphology by Halle (1973), Aronaff (1976), and Scalise (1984). Some examples of words were found in "Satua Bali Tales From Bali". The words were classified into words with prefixes, infix, suffixes and confix. In the data found that there were affixes found in the beginning of the word basic (prefix), inserts on the word (infix), suffix on the word base (suffix) or prefix and suffix that appeared together in the word base (confix). In the data also found the word that experienced nasalization process. In the prefix analysis found the fair form, potential and unnatural forms. In the infix analysis only found the fair form. In the suffix analysis found an unusual inverse form in the data. Unusual (strange) inverse forms can cause problems, because in society, those forms are not commonly used. In the confix analysis there was a reasonable invention. There was also a word that experienced a process of nasalization. For example the form of nepukin "see".